(untitled) (Research, Society and Development, 2022)
Oral mucositis is a frequent complication of antineoplastic treatment in cases of head and neck tumors. The aim of this article was to report a clinical case of a patient diagnosed with malignant neoplasm of the oropharynx undergoing radiotherapy and chemotherapy and the effects of photobiomodulation in the prevention and treatment of oral mucositis. Photobiomodulation applied for preventive purposes was carried out two to three times a week with a diode laser, with a wavelength of 660nm, 100mW, 1J per point, in contact mode, on the entire oral mucosa. The associated red (660nm) and infrared (808nm) lasers, totaling 1 J per point, were applied for therapeutic purposes. Oral mucositis severity, pain and quality of life were assessed by the following means: WHO oral mucositis severity scale, visual analogue pain scale (VAS) and EOTRC-35 and OHIP 14 quality of life questionnaires. It was concluded that photobiomodulation showed a positive effect on the patient’s quality of life and pain control. Photobiomodulation proved to be effective in preventing oral mucositis in a high degree of severity and promoted clinical remission of the lesions after approximately two sessions of application.